Concussion vs. resignation by submission: Technical–tactical behavior analysis considering injury in mixed martial arts - Miarka, Bianca; Soto, Dany A. Sobarzo; Aedo-Muñoz, Esteban A.; Maurício, Clóvis A.; Müller, Vanessa T.; Bragazzi, Nicola L.; Brito, Ciro José (Frontiers in Neurology, 2022)
This research verified technical-tactical actions during the MMA fights to generate serious enough injury to stop the MMA round, determining technical-tactical potential risk factors for injury in official MMA combats, according to Concussion or Resignation per Submission. A total of 990 rounds with concussions and 627 resignations per submission were considered with severe injury (i.e. a fight ended by a doctor or referee). All injuries were diagnosed and managed by attending ringside physicians during the MMA fights and rounds and had a continuous technical-tactical behavior analysis, p≤0.05. The leading cause of concussion was due to head trauma ( 90%), with higher dependence on head strikes scored actions. Comparisons between Concussion and Resignation per Submission combats demonstrated differences between distance head strikes actions [13(6;25) vs. 9(4;18) frequencies], clinch head strikes actions [1(0;4) vs. 1(0;3) frequencies], ground head strikes actions [1(0;8) vs. 2(0;10) frequencies] and takedowns actions [0(0;1) vs. 1(0;2) frequencies]. This information may provide significant evidence regarding the doctor stoppage in concussion combats and when it could be called by officials supervising MMA.